Adaptive 3D Self‐Assembly of Colorectal Cancer Cells With Unchanged Tumor Phenotype and Drug Sensitivity - Yong Zhang; Yang Liu; Yang Yang; Yiwei Li; Lei Liu; Yang Huang; Weiting Zhao; Yong Liu; Minghao Zhang; Yunshan Zhao; Chenggang Li (Cancer Medicine)
ABSTRACT Background Three‐dimensional (3D) self‐assembly of organoids or tumoroids based on 3D rebuilding environment (3DRE) aims to preserve the biological characteristics of original tumors, but whether the self‐assembly process is influenced by 3DREs remains unknown. We here compared the colorectal cancer (CRC) tumoroids cultured using different 3DREs, including dome culture (DG), ultra‐low adherence culture without Matrigel(UA) or with Matrigel (UAG), and hanging‐drop without Matrigel (HD) and with Matrigel (HDG). Methods CRC cells were cultured to form tumoroids using DG, UA, UAG, HD, and HDG, respectively. The differences between these tumoroids were examined using light observation, histological staining, RNA sequencing, and drug sensitivity testing. Results The CRC cells aggregated with each other and formed larger, converged tumoroids in the UA and the HD compared to the Matrigel. Histochemical examination revealed that the tumoroids maintained the CRC‐specific characteristics of forming lumens and biomarkers, but the number of lumens decreased, and the cell arrangement was in disorder with increasing impetus of 3DREs that promote cell aggregation ranging from DM, UA to HD. RNA sequencing revealed that the tumoroids retained a similar gene expression pattern, but the oncogenes related to metastasis and poor prognosis were upregulated, and development and morphogenesis‐related genes were downregulated when cultured in the UA and HD compared to the Matrigel. However, the drug sensitivity test showed that the tumoroids, regardless of the methods they were derived, maintained similar sensitivity to drugs. Conclusions We demonstrated that CRC tumoroids developed towards disordered self‐assembly in adaptation to the environment without a matrix, but this adaptation did not alter tumor‐specific phenotypes and drug sensitivity.